2022
DOI: 10.1029/2021gl096108
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of the East Asian Cold Surge and Their Impacts on El Niño

Abstract: Case studies have shown that the East Asian cold surge (CS) in winter exerts considerable impact on the development of El Niño by changing the surface wind over the western equatorial Pacific. However, a statistical assessment of the conditions under which the CS is more likely to make such an impact is lacking. Our statistical analysis shows that the CS can be divided into two types with respect to their prevailing area. The western CS type passing through the South China Sea rarely influences the equatorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Unfortunately, present climate models can hardly simulate HFPs in a realistic manner due to their multiplicative nature 7 , as they are closely related to various synoptic and sub-seasonal processes. For example, WWBs are found to be associated with the western Pacific tropical cyclones [31][32] , East Asian cold surge [33][34] , and the Madden-Julian Oscillation [35][36] . Since WWBs are modulated by ENSO with stronger and more frequent bursts to occur during large El Niño events, it is possible to formulate semi-stochastic, environment-dependent parameterization for them 37 .…”
Section: Forecast Uncertainty Due To Hfpsmentioning
confidence: 99%
“…Unfortunately, present climate models can hardly simulate HFPs in a realistic manner due to their multiplicative nature 7 , as they are closely related to various synoptic and sub-seasonal processes. For example, WWBs are found to be associated with the western Pacific tropical cyclones [31][32] , East Asian cold surge [33][34] , and the Madden-Julian Oscillation [35][36] . Since WWBs are modulated by ENSO with stronger and more frequent bursts to occur during large El Niño events, it is possible to formulate semi-stochastic, environment-dependent parameterization for them 37 .…”
Section: Forecast Uncertainty Due To Hfpsmentioning
confidence: 99%
“…Of note is that the AM and SM are consistently observed in both the annual cycle and interannual variability (e.g., in period 1948–1979 and 1948–2010 as reported) of the HC, inferring that the AM and SM are not sensitive to the sample length. Meanwhile, considering that the meridional distribution of HC is subjected to the underlying meridional gradient of tropical SST (Feng et al., 2023; E. Schneider & Lindzen, 1977), an equatorially asymmetrical/symmetrical SST distribution would associate with equatorially asymmetrical/symmetrical HC anomalies. It is established that the AM variation is attached to SST over tropical Indian Ocean (Feng et al., 2013; Ma & Li, 2008), whose formation is due to the inhomogeneous warming trend over this region (J. Li & Feng, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Early pilot studies by Chang et al [12,13] revealed the extratropical-tropical interaction processes associated with the cold surges: immediately after the cold surge, the convection in the equatorial South China Sea intensifies, which further strengthens the local East Asian Hadley circulation and the two (Indian and Pacific Ocean) Walker circulations. Most of the cold surges last less than 4 days, and a few can persist more than 5 days [14][15][16]. Cold air outbreak events can be classified into three categories according to their propagation characteristics, two of which reach low latitudes (less than 30 • N) that can significantly enhance the rainfall in the equatorial South China Sea [15].…”
Section: Introductionmentioning
confidence: 99%